Lời giải:
Ta có:
$x^3-y^3=3x-1-(3y-1)=3(x-y)$
$\Leftrightarrow (x-y)(x^2+xy+y^2)-3(x-y)=0$
$\Leftrightarrow (x-y)(x^2+xy+y^2-3)=0$
Vì $x,y$ khác nhau nên $x-y\neq 0$. Do đó $x^2+xy+y^2-3=0$
$\Rightarrow x^2+xy+y^2=3(1)$
Hoàn toàn tương tự: $y^2+yz+z^2=3(2); z^2+xz+x^2=3(3)$
Lấy $(1)-(2)$ thu được:
$x^2+xy-yz-z^2=0$
$\Leftrightarrow (x-z)(x+z+y)=0\Rightarrow x+y+z=0$ (do $x-z\neq 0$)
$\Rightarrow (x+y+z)^2=0$ hay $x^2+y^2+z^2+2(xy+yz+xz)=0$
Khi đó:
Lấy $(1)+(2)+(3)$ ta có:
$2(x^2+y^2+z^2)+xy+yz+xz=9$
$\Leftrightarrow \frac{3}{2}A+\frac{x^2+y^2+z^2+2(xy+yz+xz)}{2}=9$
$\Leftrightarrow \frac{3}{2}A+0=9\Rightarrow A=6$